2019
DOI: 10.1186/s12909-019-1501-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an evidence-based practice education program using multifaceted interventions: a quasi-experimental study with undergraduate nursing students

Abstract: Background Although Evidence-Based Practice (EBP) should be introduced early on in nursing education to develop students’ independence and self-learning ability, there are few such courses for undergraduate nursing students in Korea. This study examined the effects of the EBP education program for undergraduate nursing students (EBP-EPUNS) on nursing students’ knowledge, skills, attitudes, competencies, and future use of EBP. Methods A quasi-experimental study design wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 33 publications
6
48
0
15
Order By: Relevance
“…Results of the present study revealed that there was positive statistically significant correlation between total knowledge and total practices pre and post program.This result is agreed with Kim et al,(2019) [27]who studied "Effects of an evidence-based practice education program using multifaceted interventions: a quasi-experimental study with undergraduate nursing students and concluded thatThe EBP education program was effective in improving the knowledge, skills, attitudes, competencies, and future use of EBP among nursing students.…”
Section: H-results Disseminatingsupporting
confidence: 88%
“…Results of the present study revealed that there was positive statistically significant correlation between total knowledge and total practices pre and post program.This result is agreed with Kim et al,(2019) [27]who studied "Effects of an evidence-based practice education program using multifaceted interventions: a quasi-experimental study with undergraduate nursing students and concluded thatThe EBP education program was effective in improving the knowledge, skills, attitudes, competencies, and future use of EBP among nursing students.…”
Section: H-results Disseminatingsupporting
confidence: 88%
“…Ten studies used valid instruments to assess the EBP knowledge, attitudes and beliefs. Among the studies, three of them used the EBP-COQ questionnaire [ 29 , 30 , 31 ], one the S-EBPQ tool [ 32 ], one the EBASE survey [ 33 ] and one the KAB questionnaire [ 34 ]. Two studies were focused on research and, more specifically, one on attitudes toward research and one on confidence in research and EBP belief [ 26 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CASP score ranged from 1 to 9. One study had a CASP score of nine [ 29 ], four studies had a score of four [ 28 , 30 , 35 , 38 ], two studies [ 36 , 39 ] had a score of one and four studies a CASP score of three [ 26 , 40 , 41 , 42 ]. Additionally, by two studies had a score of five [ 34 , 43 ], six [ 32 , 44 ] and seven [ 31 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations